Analysis of wood thermal degradation using 2D correlation of near infrared and visible-light spectroscopy. Issue 5 (October 2019) - Mahdiyanti, Siti Hanifah; Inagaki, Tetsuya; Tsuchikawa, Satoru
Wood changes its properties, especially color, as a result of thermal degradation. In this study, change in wood properties due to thermal degradation have been studied using the nondestructive test methods of near infrared spectroscopy, CIELAB color measurement, visible-light spectroscopy, and Arrhenius time–temperature superposition. Arrhenius time–temperature superposition allowed analysis of near infrared and visible-light spectra, and color parameters to predict thermal degradation and color change of wood at 120–180℃ for 6 min to nine months duration. Two-dimensional correlation spectroscopy for the complementary analysis of near infrared and visible-light spectroscopy was applied to investigate chemical changes during wood thermal degradation that cause the observed color change. Visible-light spectroscopy with CIELAB color measurement was used to obtain information on color changes, and near infrared spectroscopy was applied in the measurement of chemical changes during thermal degradation. Changes in spectral intensities in 2D correlation spectroscopy indicated that different chemical components are responsible for color change during heat treatment and accelerated aging of wood. With dry-thermal treatment, the hemicellulose content decreased following a color change, whereas cellulose and lignin/extractives decreased with hygro-thermal treatment.